Family members' satisfaction with the care flow in the Pediatric Emergency Department - Giselle Pinto de Oliveira Sá Macedo; Maria D'Innocenzo (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To evaluate the satisfaction index of the pediatric patient's caregiver (person responsible for the child) regarding the waiting time for the care flow in an emergency service. Method: A prospective, cross-sectional, quantitative study with 300 family members in the Pediatric Emergency Department of a general hospital. An instrument was used to analyze the service flow, waiting time and satisfaction evaluation. Descriptive statistical analysis was performed. Results: The satisfaction index of caregivers was statistically significant (p<0.05) the lower was the waiting time for patient screening, care by the doctors and for receiving the prescribed medication. Caregivers who took their children to the emergency department because of the disease (p -0.029) or because they did not find doctors in other hospitals (p-0.021) were satisfied with the waiting time for this service. Conclusion: The quality of care is evaluated as satisfactory by caregivers when children are treated quickly in the Pediatric Emergency Department.